(3cJGH GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hGYXe eG jMJGL Edjg GSJaQGZ GdeQI GdUaQi hGdOe hcPdc bO jchf LehO HQh eDde s
(3BNQgG (B:s
(3chi HGdPgH GdCMeQ ehVY GdOe cdjkG TOjOkG djLQi GdOe efg hGddg CYde hGddg GdTGai s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3aUd abW ef GdbGfhf dGHf SjfGs
(3jdjg GdYOjO ef GdhUaGJ ef cJGH SGHhQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1311s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs